Algeria : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Algeria. (IMF Staff Country Reports; Country Report ;, 2017)
This 2017 Article IV Consultation highlights Algeria's continued challenges posed by lower oil prices. Overall economic activity was resilient, but growth in the nonhydrocarbon sector slowed to 2.9 percent in 2016, partly under the effects of spending cuts. Inflation increased from 4.8 percent in 2015 to 6.4 percent in 2016 and stood at 7.7 percent year over year in February 2017. Unemployment was 10.5 percent in September 2016 and remains particularly high among youth (26.7 percent) and women (20.0 percent). Despite fiscal consolidation in 2016, the fiscal and current account deficits remained large, and public debt increased, reflecting in part the assumption of government-guaranteed debt. International reserves, while still ample, have declined rapidly.